Sustainability of large-scale implementation of shared decision making with the SHARE TO CARE program - Stolz-Klingenberg, Constanze; Bünzen, Claudia; Coors, Marie; Flüh, Charlotte; Margraf, Nils G.; Wehkamp, Kai; Clayman, Marla L.; Scheibler, Fueloep; Wehking, Felix; Rüffer, Jens Ulrich; Schüttig, Wiebke; Sundmacher, Leonie; et al. (Frontiers in Neurology, 2022)
Introduction SHARE TO CARE (S2C) is a comprehensive implementation program for shared decision making (SDM). It is run at the University Hospital Schleswig-Holstein (UKSH) in Kiel, Germany, and consists of four combined intervention modules addressing healthcare professionals and patients: (1) multimodal training of physicians (2) patient activation campaign including the ASK3 method, (3) online evidence-based patient decision aids (4) SDM support by nurses. This study examines the sustainability of the hospital wide SDM implementation by means of the Neuromedical Center comprising the Departments of Neurology and Neurosurgery. Methods Between 2018 and 2020, the S2C program was applied initially within the Neuromedical Center: We implemented the patient activation campaign, trained 89% of physicians (N = 56), developed 12 patient decision aids and educated two decision coaches. Physicians adjusted the patients' pathways to facilitate the use of decision aids. To maintain the initial implementation, the departments took care that new staff members received training and decision aids were updated. The patient activation campaign was continued. To determine the sustainability of the initial intervention, the SDM level after a maintenance phase of 6–18 months was compared to the baseline level before implementation. Therefore, in- and outpatients received a questionnaire via mail after discharge. The primary endpoint was the “Patient Decision Making” subscale of the Perceived Involvement in Care Scale (PICSPDM). Secondary endpoints were an additional scale measuring SDM (CollaboRATE), and the PrepDM scale, which determines patients' perceived health literacy while preparing for decision making. Mean scale scores were compared using t-tests. Results Patients reported a significantly increased SDM level (PICSPDMp = 0.02; Hedges' g = 0.33; CollaboRATE p = 0.05; Hedges' g = 0.26) and improved preparation for decision making (PrepDM p = 0.001; Hedges' g = 0.34) 6–18 months after initial implementation of S2C. Discussion The S2C program demonstrated its sustainability within the Neuromedical Center at UKSH Kiel in terms of increased SDM and health literacy. Maintaining the SDM implementation required a fraction of the initial intensity. The departments took on the responsibility for maintenance. Meanwhile, an additional health insurance-based reimbursement for S2C secures the continued application of the program. Conclusion SHARE TO CARE promises to be suitable for long-lasting implementation of SDM in hospitals.